Involvement of the heparanase procoagulant domain in bleeding and wound healing. (4th June 2017) - Crispel, Y.; Ghanem, S.; Attias, J.; Kogan, I.; Brenner, B.; Nadir, Y.
Abstract : Essentials Heparanase forms a complex with tissue factor and enhances the generation of factor Xa. The present study was aimed to identify the procoagulant domain of heparanase. Procoagulant peptides significantly shortened bleeding time and enhanced wound healing. Tissue factor pathway inhibitor (TFPI)‐2 derived peptides inhibited the procoagulant peptides. Summary: Background: Heparanase, which is known to be involved in angiogenesis and metastasis, was shown to form a complex with tissue factor (TF) and to enhance the generation of activated factor X (FXa). Our study demonstrated that peptides derived from TF pathway inhibitor (TFPI)‐2 impeded the procoagulant effect of heparanase, and attenuated inflammation, tumor growth, and vascularization. Aims: To identify the procoagulant domain in the heparanase molecule, and to evaluate its effects in a model of wound healing that involves inflammation and angiogenesis. Methods: Twenty‐four potential peptides derived from heparanase were generated, and their effect was studied in an assay of FXa generation. Peptides 14 and 16, which showed the best procoagulant effect, were studied in a bleeding mouse model and in a wound‐healing mouse model. Results: Peptides 14 and 16 increased FXa levels by two‐fold to three‐fold, and, at high levels, caused consumption coagulopathy. The TFPI‐2‐derived peptides explored in our previous study were found to inhibit the procoagulant effect induced by peptides 14 and 16. In the bleeding model, time to clot formation was shortened by 50% when peptide 14 or peptide 16 was topically applied or injected subcutaneously. In the wound‐healing model, the wound became more vascular, and its size was reduced to one‐fifth as compared with controls, upon 1 week of exposure to peptide 14 or peptide 16 applied topically or injected subcutaneously. Conclusions: The putative heparanase procoagulant domain was identified. Peptides derived from this domain significantly shortened bleeding time and enhanced wound healing.